Základní problémy teorie spravedlnosti - Bubík, Tomáš (Univerzita Pardubice, 2003)
This paper focuses on the basic problems relevant for the discussion on the theory of justice. Rather than analyzing theories of justice by different authors, it concentrates on the thematic solution of the problems. Discussing the idea of order as a basic premise for the concept of authority, the introduction deals witch features of justice based on authority. It also analyzes the importance of fysis, language, and law for justice as well as the role of the virtue of justice in the formation of a just commune - polis, an issue already debated by ancient philosophers. The paper compares two typical forms of justice - communicative and distributive - and concludes with the issue of justice as fairness and with the relationship of justice and love.
Keywords: spravedlnost; filosofické hledisko; historický vývoj